The Self-care Potential of Patients with ACS in Nakhon Si Thammarat Province - Boonrapheng, Patthinan; Jantasuwan, Rachadaporn; Kusol, Kiatkamjorn; Eksirinimit, Thidarat (Science, Technology, and Social Sciences Procedia, 2025)
This study was a part of a larger research project titled “The Effectiveness of a Self-care Potential Development Program Using Social Support on Major Adverse Cardiovascular Events (MACE) within 30 Days Post-Hospital Discharge in Nakhon Si Thammarat Province.” The present phase employed a descriptive research design to explore the self-care potential of patients with acute coronary syndrome (ACS). The sample consisted of 72 ACS patients who had been admitted to a secondary hospital in Nakhon Si Thammarat Province. The sample size was calculated using the G*Power software. The inclusion criteria were as follows: 1) patients diagnosed with ACS, based on ICD-10 codes I20–I259, between September and December 2024, and scheduled for hospital discharge; 2) aged 18 years or older; 3) no speech or hearing impairments; 4) had a primary caregiver; and 5) voluntarily consented to participate in the study. The exclusion criterion was incomplete responses to the questionnaires or assessment forms. The research instruments included: 1) A personal information questionnaire, 2) A health status assessment tool (Content Validity Index [CVI] = 0.85), and 3) A self-care behavior assessment form (CVI = 0.85; Cronbach’s alpha coefficient = 0.78). Data analysis of demographic characteristics, health status, and self-care capacity was performed using descriptive statistics, including mean, standard deviation (SD), frequency, and percentage. The study results indicated that the participants had a mean age of 66.65 years (SD = 14.78). The majority were male (72.22 %) and married (59.72 %). Most had completed primary education (66.67 %) and had an average monthly income of 7,441.67 THB (SD = 4,760.45). A total of 36.11 % were unemployed. Regarding clinical characteristics, the majority of participants were diagnosed with non-ST-elevation myocardial infarction (NSTEMI) (83.33 %), followed by ST-elevation myocardial infarction (STEMI) (6.95 %) and unstable angina (9.72 %). Comorbidities were present in 84.72% of participants, with hypertension being the most common (72.13 %), followed by cardiovascular disease and dyslipidemia, both at 55.74 %. The mean BMI was 24.02 kg/m² (SD = 5.13), with most participants falling within the normal range (47.23 %), followed by those classified as overweight or obese (45.83 %). Regarding overall self-care capacity, 58.33 % of the participants demonstrated a good to very good level, while 38.89 % exhibited a moderate level. When analyzed by domain, the proportions of participants with good to very good self-care capacity were as follows: 61.11 % for medication adherence, 66.67 % for self-management, 84.72 % for stress, anxiety, and depression management, and 77.77 % for sleep quality. For cardiac rehabilitation, most participants were at a moderate level (54.16 %), with 22.22 % at a low to fair level. In the domain of diet and fluid intake, 37.49 % were at a low to fair level, and 30.56 % were at a moderate level. Based on the research findings, relevant stakeholders are encouraged to implement the program for patients with ACS, with a particular emphasis on cardiac rehabilitation and diet and fluid intake. Strengthening these areas may help prevent the occurrence of MACE in ACS patients.